High throughput gene expression profiling of yeast colonies with microgel-culture Drop-seq. Issue 10 (25th April 2019) - Liu, Leqian; Dalal, Chiraj K.; Heineike, Benjamin M.; Abate, Adam R.
Abstract : We describe isogenic colony sequencing (ICO-seq), a massively-parallel strategy to assess the gene expression profiles of large numbers of genetically distinct yeast colonies. Abstract : Yeast can be engineered into "living foundries" for non-natural chemical production by reprogramming them via a "design-build-test" cycle. While methods for "design" and "build" are relatively scalable and efficient, "test" remains a bottleneck, limiting the effectiveness of the procedure. Here we describe isogenic colony sequencing (ICO-seq), a massively-parallel strategy to assess the gene expression, and thus engineered pathway efficacy, of large numbers of genetically distinct yeast colonies. We use the approach to characterize opaque-white switching in 658 C. albicans colonies. By profiling the transcriptomes of 1642 engineered S. cerevisiae strains, we assess gene expression heterogeneity in a protein mutagenesis library. Our approach will accelerate synthetic biology by allowing facile and cost-effective transcriptional profiling of large numbers of genetically distinct yeast strains.